Retardo do diagnóstico da tuberculose em pessoas idosas: discursos de enfermeiros assistenciais - Trigueiro , Janaína Von Söhsten (2016)
Introduction: The permanence of tuberculosis (TB) is continuous, and the early detection of cases is essential for the successful reach of its control. However, it is noted that the lack of agility in the diagnosis stands out as one of the great challenges of management as well as for health workers in reducing the incidence of the disease in Brazil. Among the most vulnerable demands, it is imperative to think of elderly users, because the diversity of factors that are inherent to them is even more important to be considered, as the problem of delayed diagnosis is aggravated when associated with patients at more advanced ages. Objective: To analyse the causes of delayed diagnosis of TB in the elderly, based on the effects of senses contained in the speeches of nursing assistants in João Pessoa-PB. Method: A qualitative study that had as theoretical-methodological contribution the Discourse Analysis of French slope, focusing on the principle of integrality and the thought of the Levinasian Alterity. Held between October 2015 and February 2016, it had as collaborators 17 assisting nurses working in the Family Health Strategy of the city of João Pessoa-PB and in the Clementino Fraga Hospital Complex. The project was submitted and approved by the Research Ethics Committee of the Centro de Ciências da Saúde of Universidade Federal da Paraíba under protocol number 0461/13 and CAAE nº 15845613.1.0000.5188. Results: The effects of mobilized senses explained the integral care that the biomedical model prevails, but there is an attempt to break its hegemony, based on humanized actions. Regarding the causes of delayed diagnosis of TB in the elderly, the subjects evidenced a diversity of factors that directly and indirectly influence the diagnostic slowness. Among them, the biological issues of the elderly, the socio-historical prejudice of the disease and the frailties of the work process developed in the three levels of attention to health were highlighted. Conclusion: Based on the plurality of meanings that involve the elderly with TB as well as their inexhaustible subjectivity, it is imperative that RAS offers a structure that meets the diversity of needs that are peculiar to them. The care must be simultaneously individual and collective, having as pillar the union of the integrality and the Alterity.